2023
DOI: 10.1021/acs.jafc.2c07963
|View full text |Cite
|
Sign up to set email alerts
|

Response of Odorant Receptors with Phenylacetaldehyde and the Effects on the Behavior of the Rice Water Weevil (Lissorhoptrus oryzophilus)

Abstract: The rice water weevil (RWW), Lissorhoptrus oryzophilus Kuschel (Coleoptera: Curculionidae), is a destructive rice pest that threatens the rice industry worldwide. Odorant receptors (ORs) and odorant receptor coreceptors (Orcos) play an important role in the process of insects' whole life activities; however, there are no related functional studies on RWW. On this basis, a heterologous study of LoryOR20/LoryOrco in Xenopus laevis oocytes was performed to detect the effects of certain natural compounds on RWWs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…To verify the function of PstrOR17 in vivo, we employed RNAi-based gene silencing to silence PstrOR17 expression. Recently, RNAi has been successfully used in functional studies for downregulation of target genes for several insect species, particularly chemosensory genes [28,33,50]. Numerous studies reported that knockdown of ORs consistently produces attenuated behavioral responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To verify the function of PstrOR17 in vivo, we employed RNAi-based gene silencing to silence PstrOR17 expression. Recently, RNAi has been successfully used in functional studies for downregulation of target genes for several insect species, particularly chemosensory genes [28,33,50]. Numerous studies reported that knockdown of ORs consistently produces attenuated behavioral responses.…”
Section: Discussionmentioning
confidence: 99%
“…The electroantennogram (EAG) procedure was followed as previously described with minor modifications [33]. Briefly, the head was excised and the proximal tip of the antenna was finely transected.…”
Section: Electroantennogrammentioning
confidence: 99%
See 1 more Smart Citation
“…As an excellent indicator of flavor, PAA is a common compound emitted from numerous flowering plant species. Several behavioral studies have shown that PAA is extensively attractive to various agricultural insect pests. , Thus, PAA could be a potential trap component for controlling S. frugiperda infestation.…”
Section: Discussionmentioning
confidence: 99%
“…Phenylacetaldehyde (PAA) is a commonly emitted compound by numerous flowering plant species correlated with nectar sugar and pollen amounts. Additionally, PAA is also released by many important crops like maize, cotton, and tomato. Several studies suggest that PAA plays an important role in chemosensory behavior in different groups of insects. A Y-tube behavioral assay indicates that PAA significantly attracts rice water weevil ( Lissorhoptrus oryzophilus ) adults .…”
Section: Introductionmentioning
confidence: 99%